PERILAKU PERUSAHAAN DALAM PEMANFAATAN FREE CASH FLOW - Ernie Riswandari (Jurnal Akuntansi Bisnis, 2017)
The objective of this article is to explain how company behaviors to manage free cash flow. Accordingly, free cash flow is the amount of cash that a company has left over after it has paid all of its expenses, including investments. The shareholder as the owner of the company delegate authority to the manager (agent), so that it creates variousity of interest among  them the so-called `Agency Conflict'. The Shareholder and manager always maximize their income so that it can bring  company behavior out reflecting on their policy.Keyword;  free cash flow, debt policy, dividend policy, agency cost.